Tracing Back the Humor Style of the Eighth and Twentieth Century Texts of Abunawas - Lesmana, Maman (TAWARIKH, 2011)
ABSTRACT: This article contains responses toward opinions which say that humor by Abunawas prevailing in Indonesia is fictive and not from Arab. After analyzing texts of the eighth and twentieth century of Abunawas, it is clear that based on the aspects of fictional indications either formal or referential, ill-locution and per-locution, as well as imaginative and non imaginative, texts of Abunawas in the twentieth century is more fictive than the texts of the eighth century. In addition, this article shows that either texts of the eighth or twentieth century both contain humor and non humor. The texts that consist of joking indicate that the type of humor in the eighth century is less than the twentieth century. Based on the categorization mentioned above, this article also tries to say that humors prevailing in the eighth century texts of Abunawas are mostly classified into âsuperiority theoriesâ; whilst the twentieth century texts are correspond to theories proposed by D.H. Monro (1988).KEY WORDS: Humor and non humor, Abunawas, imaginative and non imaginative, and eighth and twentieth century texts.Â Â About the Author: Dr. Maman Lesmana is a Lecturer at the Arabic Studies Program, Department of Area Studies, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok 16412, West Java, Indonesia. He can be reached at: malessutiasumarga@yahoo.com Â Â How to cite this article? Lesmana, Maman. (2011). âTracing Back the Humor Style of the Eighth and Twentieth Century Texts of Abunawasâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.161-174. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 24, 2011); Revised (March 27, 2011); and Published (April 28, 2011).